Longitudinal assessment of myocardial edema following experimental acute myocardial infarction using a comprehensive CMR protocol. (3rd October 2022) - Jablonowski, R; Nordlund, D; Xanthis, C; Bidhult, S; Kopic, S; Berg, J; Engblom, H; Aletras, A H; Arheden, H
Abstract: Background: Preclinical and clinical data following acute myocardial infarction (MI) and reperfusion have shown a bimodal pattern of edematous myocardium at risk (MaR) on cardiovascular magnetic resonance (CMR) imaging during the first week [1, 2]. In contrary, there have also been data demonstrating that MaR is stable during the first week in patients using contrast-enhanced steady-state free precession (CE-SSFP) imaging [3]. Purpose: To use a comprehensive CMR protocol to assess the dynamics of edematous MaR during the first week following acute experimental MI. Methods: Acute myocardial ischemia was induced in seven pigs by endovascular balloon occlusion in the left anterior descending artery with reperfusion after 40 minutes. CMR was performed at baseline, at 120 minutes, 24 hours and seven days post-reperfusion on a 1.5T scanner. The CMR protocol comprised of a prototype T2-SSFP sequence where two experiments with 16 echo times (T2 mapping16) and with 10 echo times (T2 mapping10) [1] were performed. After contrast administration, a short-axis CE-SSFP stack and late gadolinium enhancement (LGE) images were acquired. T2-maps were acquired in a mid-apical ventricular short-axis slice corresponding to the same anatomical level at all time points. All image analysis was performed using designated software. Severity of MaR was measured by placing a region of interest in the ischemic area on T2 maps and extent of MaR was assessed by delineating hyperintense areas in CE-SSFP short-axis stacks. Data is presented as mean ± SD and one-way ANOVA was used followed by Tukey's multiple comparison test. Results: An example of all acquired CMR sequences is shown in Figure 1, with red arrows depicting the extent of edematous MaR. Figure 2 shows the severity of MaR by T2 values from T2 mapping16 where T2 values were significantly lower at 24 hours compared to 120 minutes post-reperfusion (P<0.05). However, no significant difference was seen at 120 minutes or at 24 hours compared to T2 values at seven days (P=0.46 and P=0.35). No difference at baseline (47±3 ms vs 49±3 ms, P=0.10) was observed when comparing T2 mapping16 against T2 mapping10 but a significant difference between the time points 120 min (80±8 ms vs 69±7 ms, P=0.02), 24 h, (69±9 ms vs 54±4 ms, P=0.03), and seven days (76±10 ms vs 67±5 ms, P=0.04) post-reperfusion. There was no statistically significant difference between T2 values post-reperfusion using T2 mapping10 (P=ns). The extent of myocardium at risk assessed by CE-SSFP did not show a bimodal pattern of edema, but rather a significantly lower extent at seven days compared to the extent at 120 minutes and 24 hours (P<0.05). Conclusion: The severity and extent of edematous myocardium at risk does not follow a bimodal pattern over the course of one week. However, absolute T2 values differ between T2 mapping sequences and therefore a standardization of a CMR protocol for the assessment of MaR is of importance. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): The Swedish Heart-Lung Foundation and The Medical Faculty of Lund University (ALF)